Technical Nuances of Ventriculoatrial Shunt Using Seldinger Technique for Percutaneous Insertion of Distal Shunt Catheter - Thirumal, Yerragunta; Yerramneni, Vamsi Krishna; Kanala, Ram Nadha Reddy; Karanth, Vishwa Kumar; Kolpakwar, Swapnil; Namdev, Vikram Manure; VV, Rajesh Babu (Indian Journal of Neurosurgery, 2020)
Introduction One of the most seen neurosurgical complications is the ventriculoperitoneal (VP) shunt failure. The cause can be often due to peritoneal malabsorption of cerebrospinal fluid. The next safer alternative is to place a ventriculoatrial (VA) shunt. Various methods of access to the right atrium had been described. The percutaneous method of insertion of distal catheter using Seldinger technique is a safer alternative to open method. We describe the percutaneous insertion of distal catheter using Seldinger technique, modifications in the method, and specific tools required for the insertion.Clinical History The patient is a 22-year-old male who is a known case of tubercular meningitis with recurrent failure of VP shunt due to malabsorption at peritoneal end of catheter. During the last hospital visit, he presented with altered sensorium and computed tomography scan brain showed ventriculomegaly. He was planned for VA shunt placement.Surgical Technique The insertion of ventricular end of the catheter is similar to any other shunt placement. The internal jugular vein (IJV) was punctured using introducer needle and guide wire was placed in the IJV at the level of T6-T7 and the serial dilators passed on the guide wire for creating a track for passage of shunt catheter. The shunt catheter was passed over the guide wire to the desired vertebral level and distal shunt catheter is connected proximally to the shunt catheter in the neck.Conclusion The percutaneous insertion of distal catheter with serial dilators using Seldinger technique is a safe and effective method for VA shunt placement.
Keywords: ventriculoatrial shunt; Seldinger technique; distal end